Tax Amnesty Study in the Framework of Maqashid Syariah to Increase Tax Revenue - Andriani, Reski; Bulutoding, Lince; Fadhilatunisa, Della (ISAFIR: Islamic Accounting and Finance Review, 2025)
The purpose of this study is to determine the extent to which the implementation of tax amnesty at KPP Pratama Makassar Selatan is running well, especially related to the realization of tax revenue and the level of taxpayer compliance in submitting Annual Tax Returns, which will be studied within the framework of maqashid sharia. This study uses a case study methodology and is classified as qualitative research. Based on the results of the study, the state tax industry has felt the benefits of the implementation of the tax amnesty policy. Tax revenues have increased quite significantly compared to before the tax amnesty policy was implemented. In addition, taxpayer compliance has increased as an impact of the tax amnesty program, especially in terms of submitting annual tax returns. According to Maqashid Sharia, the tax amnesty policy is in accordance with and in accordance with the concept of Islamic protection, which states that higher tax revenues indicate protection of property (hifdz al-mal) and descendants (hifdz an-nasb), while higher taxpayer compliance in submitting annual tax returns indicates protection of life (hifdz an-nafs) and protection of reason (hifdz al-aql).